2016
DOI: 10.1021/acs.biochem.5b01343
|View full text |Cite
|
Sign up to set email alerts
|

The Achilles’ Heel of “Ultrastable” Hyperthermophile Proteins: Submillimolar Concentrations of SDS Stimulate Rapid Conformational Change, Aggregation, and Amyloid Formation in Proteins Carrying Overall Positive Charge

Abstract: Low concentrations (<3.0 mM) of the anionic surfactant sodium dodecyl sulfate (SDS) have been shown to induce the formation of amyloid fibers in more than 20 different mesophile-derived proteins in the cationic state. It is not known whether SDS has similar effects on hyperthermophile-derived proteins, which are otherwise thought to be "ultrastable" and inordinately resistant to structural perturbations at room temperature. Here, we show that low (<4.5 mM) concentrations of SDS rapidly induce the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…If the pH of a protein's environment is well below its pI, it protein possesses an overall positive charge, and is easily approached by SDS. Under these conditions, low (millimolar) concentrations of SDS bind to transform proteins into beta sheet‐based amyloids, as has now been shown with many proteins . When the pH is above the p I , and the protein possesses an overall negative charge, low millimolar concentrations of SDS are not sufficient to overcome the electrostatic repulsion, and transformation into amyloids is not observed.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…If the pH of a protein's environment is well below its pI, it protein possesses an overall positive charge, and is easily approached by SDS. Under these conditions, low (millimolar) concentrations of SDS bind to transform proteins into beta sheet‐based amyloids, as has now been shown with many proteins . When the pH is above the p I , and the protein possesses an overall negative charge, low millimolar concentrations of SDS are not sufficient to overcome the electrostatic repulsion, and transformation into amyloids is not observed.…”
Section: Discussionmentioning
confidence: 97%
“…Highly acidic proteins can be expected to repel SDS. In a recent series of papers examining the binding of SDS to proteins, it has been observed that the overall charged status of a protein is the primary determinant of the ease with which it can be approached by SDS molecules . If the pH of a protein's environment is well below its pI, it protein possesses an overall positive charge, and is easily approached by SDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During thermal unfolding beyond 45˚C, a 222-nm peak shifted towards single a 225-nm peak ( Fig 12A). Thermal stress at pH 7.0 led to the conversion of CdGSTM1 from an alpha helical structure into a cross-beta sheeted structure, which aggregated beyond 75˚C [45]. However, thermal denaturation of monomeric CdGSTM1 led to the conversion of the same alpha-helical structure to a random-coil structure ( Fig 12B).…”
Section: Thermodynamic and Spectroscopic Properties Of Dimeric And Momentioning
confidence: 98%